Perfectionism and the Threat of Grace: Reimagining Theological Principles for Healing - Burt, Henry (2024)
In this discussion, I provide a perspective on perfectionism as a spiritual struggle in such a way that challenges the consoling nature of grace. Through the case studies of a Mormon housewife, Martin Luther, and myself, I illuminate the conundrum found in a Law to ‘be perfect,’ on the one hand, and the Gospel—interpreted as a ‘Law’ to receive grace—on the other. The predicament I seek to address is: how is the perfectionist to placate both of these competing ‘Laws’? I suggest that a troublesome theology of Law and Gospel from the viewpoint of the perfectionist can be redeemed in service to them by employing Luther’s theology of ‘new decalogues.’ Luther’s concept, contextualized to the perfectionist, affirms the creativity they might apply to their theology with respect to conflicting perfectionistic concerns and strivings so that grace, in a new light, might have a fuller effect in their life.
Keywords: new decalogues; Law And Gospel; spiritual struggles; Perfectionism